Minocycline as a therapeutic option in bullous pemphigoid. - Loo, W; Kirtschig, G; Wojnarowska, F (2001)
We present a retrospective analysis of patients with bullous pemphigoid (BP) treated with minocycline in the Department of Dermatology, Churchill Hospital, Oxford between July 1986 and May 2000. More than 200 patients with BP were seen in clinic during the review period. Of these, 22 patients were treated with minocycline, mostly as adjuvant therapy. The response to treatment was assessed by clinical improvement and whether the dose of concurrent immunosuppressive drugs was subsequently reduced. A major response was seen in six patients, a minor response in 11 and no response was seen in five patients. Minocycline was discontinued in four patients because of the occurrence of side-effects. Overall analysis revealed marked clinical benefits of minocycline in BP. However, this is a non-placebo controlled study and should now be followed by a prospective double-blind controlled clinical trial.